2015
DOI: 10.1111/nmo.12734
|View full text |Cite
|
Sign up to set email alerts
|

Lack of endogenous cholecystokinin promotes cholelithogenesis in mice

Abstract: Background Celiac disease is an autoimmune enteropathy caused by a permanent intolerance to dietary gluten in genetically predisposed individuals. Cholecystokinin (CCK) release from the proximal small intestine and gallbladder emptying in response to a fatty meal are greatly reduced in celiac patients before they start the gluten-free diet, showing a genetic predisposition to gallstones. Methods To elucidate the complex pathophysiological mechanisms determining the biliary characteristic of celiac disease, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…More importantly, biliary cholesterol secretion is almost doubled in coeliac patients, indicating that hepatic hypersecretion of biliary cholesterol is a primary factor for the formation of supersaturated bile . By studying CCK knockout (KO) mice, an excellent animal model relevant to the biliary characteristic of coeliac disease, it is observed that hepatic secretion of biliary cholesterol and phospholipids, but not bile salts, is significantly increased after 56 days of lithogenic diet feeding . These abnormalities enhance biliary lithogenicity, thereby leading to rapid cholesterol crystallization and gallstone formation in CCK KO mice compared to wild‐type (WT) mice.…”
Section: Potential Lithogenic Mechanism Of Coeliac Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…More importantly, biliary cholesterol secretion is almost doubled in coeliac patients, indicating that hepatic hypersecretion of biliary cholesterol is a primary factor for the formation of supersaturated bile . By studying CCK knockout (KO) mice, an excellent animal model relevant to the biliary characteristic of coeliac disease, it is observed that hepatic secretion of biliary cholesterol and phospholipids, but not bile salts, is significantly increased after 56 days of lithogenic diet feeding . These abnormalities enhance biliary lithogenicity, thereby leading to rapid cholesterol crystallization and gallstone formation in CCK KO mice compared to wild‐type (WT) mice.…”
Section: Potential Lithogenic Mechanism Of Coeliac Diseasementioning
confidence: 99%
“…It has been found that CCK plays a role in the regulation of small intestinal motility because Cck‐1r is expressed in the smooth muscle of small intestine, which is a variable known to influence intestinal cholesterol absorption in humans . Indeed, small intestinal transit time is significantly retarded not only in CCK KO mice , but also in CCK‐1R KO mice . As a result, intestinal cholesterol absorption efficiency is significantly increased in these knockout mice.…”
Section: Potential Lithogenic Mechanism Of Coeliac Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the metabolic alterations alluded to above, there is a role for altered gallbladder motility in promoting gallstone susceptibility, evidenced by findings in both Cck KO mice and in Cckr1 KO mice (18,19). These findings, coupled with findings that CD36-dependent signaling promotes secretin and cholecystokinin (CCK) release from enteroendocrine cells (20), raised the question of whether CD36 might function more broadly in modifying gallstone susceptibility, specifically via alterations in gallbladder contractility.…”
mentioning
confidence: 99%